Ownership and Control: A Spanish Survey - Rafel Crespi-Cladera; Miguel A. Garcia-Cestona (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper analyses the ownership structure of a large sample of Spanish listed companies. The results are analysed in terms of governance implications under the agency theory context. The results show a picture with concentrated ownership where stock markets are relatively low important. Direct ownership and voting blocks, which account for indirect ownership through third companies, are larger for non-financial firms followed by families or individuals and financial firms other than banks. Nevertheless, the use of intermediate companies (pyramiding), is not frequent according to our data. Banks seem not to play the important role they did in the past and the recent privatisation reduced to a minimum level, state shareholdings on listed companies.
Keywords: G32; 330; Ownership; Control; Spain; Eigentümerstruktur; Corporate Governance; Spanien; Aktienstimmrecht